UJI VALIDITAS DAN RELIABILITAS BOREDOM PRONENESS SCALE (BPS) VERSI BAHASA INDONESIA PADA MAHASISWA PROGRAM STUDI PENDIDIKAN DOKTER FAKULTAS KEDOKTERAN UNIVERSITAS SRIWIJAYA - Wahyudi, Chandra; Prananjaya, Bintang Arroyantri (Fakultas Kedokteran Universitas Sriwijaya, 2020)
Abstract Validity and Reliability Testing of Boredom Proneness Scale Indonesian Version Amongst Faculty Medicine Sriwijaya University. Boredom is defined as a state of relatively low arousal and dissatisfaction, which is attributed to an inadequately stimulating situations. Everyone has a tendency to experience boredom. Boredom Proneness Scale (Farmer and Sunberg, 1986) is one of many scale that can measures boredom proneness. BPS hasn’t been adapted from the original language (English) in Indonesia. This study uses validity and reliability approach. Process of study divided into adaptation process and psychometric analysis process. Psychometric analysis of BPS Indonesian Version consists of Item Content Validity Analysis (I-CVI) & Scale Content Validity Index (S-CVI). BPS Indonesian Version was spread twice amongst students of Medicine Program Faculty of Medicine Batch 2016─2018. Psychometric analysis of Boredom Proneness Scale Indonesian Version as Guttman Scale was done by counting the coefficient of reproducibility (CR) and coefficient of scalability (CS). BPS Indonesian Version were obtained by adaptation process. Based on 9 experts’ appraisal in experts panel, minimum I-CVI is 0,83 (minimally accepted index 0,78) on the 10th scale and S-CVI is 0,98 (minimally accepted index 0,90). CR of BPS Indonesian Version is 0,589 (first) and 0,594 (second) which defines BPS Indonesian Version is not valid and CS of BPS Indonesian Version is obtained as 0,177 (first) and 0,188 (second) which defines BPS Indonesian Version is not appropriate to be used in study. BPS Indonesian Version is not aprropriate to be used in measuring boredom proneness in students of Medicine Program Faculty of Medicine Sriwijaya University. Keywords: Boredom Proneness Scale, Boredom, Validity, Reliability